A study on the shear strength characteristics and microscopic mechanism of coal-bearing soil under dry-wet cycles - Fan, Yakun; Zheng, Mingxin; Wu, Junhua (Frontiers in Earth Science, 2023)
The slope of coal-bearing strata distributed along the high-speed highway (railway) is affected by the atmospheric dry-wet cycles (DWC), and the collapse occurs many times during the construction of such highways, in Pingxiang city, in the province of Jiangxi. The DWC affect the strength characteristics of the unsaturated coal-bearing soil (CBS). In order to study the shear-strength characteristics of the unsaturated CBS under the DWC, the relationship between the shear strength and matric suction was analyzed by using direct shear test of the unsaturated CBS, the filter paper method of the matrix suction measurement, and the scanning electron microscope test. The internal reasons of shear strength attenuation of unsaturated CBS under DWC are revealed from microscopic perspective. The results show that the DWC at 0 to 4 times, with an increase in the water content, the clay domains expanded unevenly. Further, the clay minerals that served as the cementing junctions and soluble salts were softened and dissolved, and the bonding strength between the basic units and the cohesion of the samples decreased, so that the shear strength of unsaturated CBS samples decreased with an increase in the water content, and increased with the increase of matric suction. Under the influence of the DWC, the CBS samples slaked, the quartz matrix between the fissures slaked, and produce fragments and debris which reduced the size of large particles, and the bonding strength between the basic units was low. Therefore, the matric suction and the shear strength of the unsaturated CBS samples with the same moisture content, under the same normal pressure, decreased gradually with an increase in the number of the DWC. It is feasible to study the strength characteristics of unsaturated CBS by combining the test methods of macroscopic strength, matric suction and microstructure of soil.